EP416/#785 Pregnancy after sugery and brachytherapy for vaginal cancer – a case report. (4th December 2022) - Gerbasi, Giovana; Deckers, Paula; Kanaguchi, Giuliana; Cintra, Georgia; Maia, Maria Aparecida; Lopes, Andre
Abstract : Objectives: To report a successful pregnancy case, carried to term, after treatment for vaginal cancer. Primary vaginal cancer is infrequent, corresponding to 1–2% of all female genital tract cancer diagnoses. Treatment for vaginal cancer varies depending on tumor histology, size, location, and staging and may include one or more of the following: surgical excision, radiation therapy and/or chemotherapy. All treatments negatively affect fertility/pregnancy outcomes. Pelvic radiation therapy, even in doses < 2 Gy, may extinguish up to 50% of immature oocytes. In addition, radiotherapymay cause modifications in cervical length, loss of uterine junctional zone anatomy and lead to myometrial atrophy and fibrosis, increasing the risk for adverse pregnancy outcomes. Methods: We reviewed the medical charts of a patient who carried a pregnancy to term after surgery and brachytherapy for vaginal cancer. Results: A 28 year-old woman, presented with a 3 cm right vaginal wall tumor, diagnosed as grade 3, vaginal squamous cell carcinoma -FIGO 2009, stage IB. Computed tomography showed no evidence of lymph node spread or distant metastasis. The patient underwent surgery followed by 4 sessions of vaginal brachytherapy totaling a dose of 6 Gy at a 5 mm depth. One year and 9 months after treatment, the patient gave birth to a healthy child at 40 weeks. A C-section was needed due functional dystocia during labor. Conclusions: This is the first case report of a successful pregnancy carried to term after surgery and brachytherapy for vaginal cancer.